Muhammadiyah Jawa / Ahmad Najib Burhani; penerjemah, Izza Rohman Nahrowi; penyunting, Aditya Pratama - AHMAD NAJIB BURHANI; IZZA RAHMAN NAHROWI; ADITYA PRATAMA (Suara Muhammadiyah, 2016)
xxvii, 186 hlm. : ilus. ; 21 cm.